Sustainability and Indigenous Knowledge System among Indian Mothers: Preservation of Traditional Culture- A Comparative Study of Eco-Innovative Ethos in Urban and Rural Areas in Fatehabad District, Haryana - Rani, Shweta Rani; Singh, Jasdeep (International Journal of Humanities and Education Development (IJHED), 2024)
Sustainable practices have become a necessary aspect in the modern lifestyle. The onus of professing an eco-friendly sustainable life lies on all of us. Among the various indigenous communities, the women folk have been the traditional incubators and transmitters of knowledge relating to seed preservation and storage, food processing, indigenous health practices, etc. Such forms of knowledge are often contextual, rooted in experience and experiments but are non-codified. These women community as Indian mothers and their role in the preservation of traditional and eco-innovative methods are worth mentioning. Therefore, it becomes essential that such knowledge sharing mechanism recognizes the value of knowledge possessed by women and provides space for value-addition and the amalgamation of women’s knowledge in the global knowledge pool. The role of women in the use and preservation of traditional knowledge in the various aspects of their daily life is manifold. Indian mothers are eco-innovative due to their creativity and use various techniques to make useless resources into resourcefulness in managing the household waste by reuse and recycling. This study will examine the sustainability habits of Indian mothers, by focusing on the innovative recycling and reusing behaviour of Indian mothers and to investigate how their innovative recycling and reuse method supports sustainable development. This research, therefore, aims to highlight the various strategies used by Mothers, by adapting a comparative study between rural and urban settings, thus, identifying the differences and similarities in sustainable practise of urban and rural mothers. Also, the study will explore the myriad ways in which traditional knowledge possessed and professed by Indian mothers can be useful to modern science leading to environmental sustainability. This study employs a mixed method approach employing both quantitative and qualitative data. The online survey research method will be used to collect data from the Indian mother at Pan India level through social media platforms using google forms, online applications Instagram, WhatsApp, Gmail and LinkedIn. In addition to this, offline survey will be conducted to collect the primary data from the Indian mothers by using purposive random sampling. Primary data are collected through suitable technique such as questionnaire are prepared to collect primary responses from rural and urban mothers and Secondary data will be collected through authentic available sources. Suitable cartographic and statistical techniques will be employed to achieve the desired results. Time series analysis will be used to depict the variations in trends and for future forecasting ensuring sustainability. The obtained results will be processed using SPSS software and will be mapped using Arc GIS software. Key findings of the study indicate that the rural mothers are excellent in the recycling and reuse and heavily rely on traditional methods whereas the urban mothers are not so completely engaged in professing traditional methods due to their cosmopolitan nature in context of multifaceted tasks. Understanding the nature of Indian mothers in Sustainability practise may offer valuable insights from grassroots level however, policy makers should start some programs to support and enhance their practise. Addressing both contexts such as urban and rural areas can provide more inclusive sustainable development strategies across India.